ANALISIS PENGARUH CELEBRITY ENDORSEMENT TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Pada Pengguna Lipstik Merek Wardah di Kota Semarang) - Wahyu Novita; Budi Sudaryanto (Diponegoro Journal of Management, 2022)
The development of the cosmetic industry in Indonesia recently has had a significant impact on producers and business people. Tighter competition encourages companies to compete with each other to make products that are of interest to consumers and develop appropriate strategies in marketing products, one of which is celebrity endorsement which can increase product sales. The purpose of this study was to determine the effect of celebrity endorsement on purchase intention with brand image as an intervening variable (Study on Wardah Brand Lipstick users in Semarang City). The population in this study were users of Wardah brand lipstick in Semarang City who were at least 17 years old and had used Wardah brand lipstick at least 1 time. The number of samples used as many as 140 respondents and selected by purposive sampling technique through a questionnaire. The data obtained were then analyzed using the Analysis of Moment Structure (AMOS) version 22. The results of the study indicate that celebrity endorsement has a positive and significant effect on brand image, celebrity endorsement had no significant effect on purchase intention, and brand image has a positive and significant effect on purchase intention